Shifting paradigms: how the fight for 'universal access to AIDS treatment and prevention' supports achieving 'comprehensive primary health care for all' - Ooms Gorik (BMC, 2008)
Abstract In a recent issue of Globalization and Health, Yu et al. examine the impact of HIV/AIDS programs on health care systems. This editorial considers their position and confirms that the former actually supports the latter aim; the two approaches are not at odds with one another, but could be viewed as complementary. A key requirement towards meeting both objectives is to ensure sustained international aid.